2017
DOI: 10.1186/s13019-017-0676-3
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic significance of preoperative plasma D-dimer level in patients with surgically resected clinical stage I non-small cell lung cancer: a retrospective cohort study

Abstract: BackgroundPlasma D-dimer level, a marker of hypercoagulation, has been reported to be associated with survival in several types of cancers. The present study aimed to evaluate the prognostic significance of preoperative D-dimer levels in patients with surgically resected clinical stage I non-small cell lung cancer (NSCLC).MethodsParticipants comprised 237 patients with surgically resected clinical stage I NSCLC. In addition to factors such as age, sex, and smoking status, the association between preoperative D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
14
2
Order By: Relevance
“…Jiang et al reported that preoperative D‐D positivity (> 0.55 mg/L) is a significant and independent predictor for unfavorable disease‐free survival in NSCLC patients . A recent study conducted by Kaoru et al also revealed that an elevated preoperative D‐D level (>1.0 mg/L) is significantly associated with poor recurrence‐free survival among stage I NSCLC patients . In our study, however, neither univariate nor multilevel analyses confirmed the prognostic significance of elevated preoperative D‐D.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Jiang et al reported that preoperative D‐D positivity (> 0.55 mg/L) is a significant and independent predictor for unfavorable disease‐free survival in NSCLC patients . A recent study conducted by Kaoru et al also revealed that an elevated preoperative D‐D level (>1.0 mg/L) is significantly associated with poor recurrence‐free survival among stage I NSCLC patients . In our study, however, neither univariate nor multilevel analyses confirmed the prognostic significance of elevated preoperative D‐D.…”
Section: Discussioncontrasting
confidence: 95%
“…8 A recent study conducted by Kaoru et al also revealed that an elevated preoperative D-D level (>1.0 mg/L) is significantly associated with poor recurrence-free survival among stage I NSCLC patients. 9 In our study, however, neither univariate nor multilevel analyses confirmed the prognostic significance of elevated preoperative D-D. We believe this can be explained by the low statistical power of our study. Moreover, other more potent prognostic factors may have overshadowed its effect in the multilevel analyses.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…It is reported that D-dimer can not only affect cellular signaling systems and promote cell proliferation, but also stimulate the cellular adhesion of tumor cells to endothelial cells, affect platelets and extracellular matrix, and ultimately, induce the growth and spread of tumors (3,4). Many studies have affirmed that high levels of plasma D-dimer were associated with advanced tumor stage and poor survival of cancer patients (5)(6)(7)(8)(9)(10)(11)(12). Several researches reported that preoperative plasma D-dimer level (PDL) was an independent prognostic factor in patients with completely resected nonsmall cell lung cancer (NSCLC) (5)(6)(7), and others confirmed that the prognosis was significantly influenced by the elevated PDL in patients with colorectal cancer (8)(9)(10), esophageal cancer (11), breast cancer (12) and so on.…”
Section: Introductionmentioning
confidence: 99%